AN INTERVIEW WITH JUDITH KOHAN-MASS: ON GIFTEDNESS IN ISRAEL - Shaughnessy, Michael (Acta Scientiae et Intellectus, 2024)
There are several people who have made intellectual mark on me through the books that they wrote. But if I address the people in my life, the real people, there are two who have accompanied me along my career as mentors, both in a personal and a professional sense. The first is Professor Diane Halpern. After I read most of her books, which inspired my own work, I met her at a conference in Belfast, Ireland, and the connection we made was truly meaningful for me. Although Professor Halpern is an extremely busy woman and holds a very senior position as the Dean of Social Science at Minerva Schools at Keck Graduate Institute, she is also very human and warm. She has accompanied me through all my career decisions, and sometimes through personal decisions, too. She is without doubt my (female) role model. The second figure is Professor David Chen, who is the Dean of the School of Education at the Center of Academic Studies. In addition to being my superior, he is a constant source of intellectual and personal inspiration.